Relationship between motivation and learning outcomes in e-learning among university students in Malaysia - Chengjun, Ma; Mustakim, Siti Salina (Human Resource Management Academic Research Society, 2022)
COVID-19 pandemic has impacted the entire world, including Malaysia. Facing the increasing number of cases, educational institutions in Malaysia have forced to stop operations, and e- learning is mainly practiced among students of higher education. However, E-learning is not fully utilized in Malaysia. Some problems have emerged, and these problems are closely related to learning motivation. Hence, this research intends to determine the relationship between motivation and learning outcomes in e-learning among university students in Malaysia. 379 students from Universiti Putra Malaysia were selected using simple random sampling technique in this study. Participants were requested to complete a questionnaire that included the Instructional Materials Motivation Survey (IMMS), which was specifically built for the Attention, Relevance, Confidence, and Satisfaction (ARCS) model and the learning outcomes instrument. Descriptive and inferential statistics were used to analyse the level of variables and the relationship between these variables. Findings showed that there is a significant relationship between motivation and learning outcomes (r=.588, p=.000). The study also found that attention is a greater determiner of learning outcomes.